Evaluation of Antimutagenic Potential of Chrozophora Rottleri against Ems Induced Mutagenicity in Mice - Kavitha GC; Pallavi M; Chandrashekar Srinivasa; Chandan Dharmashekar; Bhargav Shreevatsa; Shiva Prasad Kollur; Chandan Shivamallu; Sharanagouda S. Patil; Ashiwini P (International Journal of Pharma and Bio Sciences, 2022)
The natural medicinal plant compounds derived from numerous plant extracts are being gradually used to treat a wide variety of clinical diseases. Chrozophora rottleri is a natural therapeutic herb belonging to Euphorbiaceae family, which is commonly called Suryavarti. Various studies reported that this medicinal plant has a wide variety of medicinal values, including antimicrobial, antioxidant, antifungal, and antispasmodic activity. Still, there is no report about antimutagenic and mutagenic activity. The aim of the study is to determine the antioxidant and antimutagenic effects of C. tinctoria extracts. On that account, the current study is to isolate compounds from various solvents of Chrozophora rottlerin leaves extracts. The obtained extracts were preliminary subject to phytochemical screening to identify various phytoconstituents and further EMS (Ethyl Methane sulfonate) induced bone marrow chromosomal aberration which has been used to evaluate the in vivo antimutagenic potentials of the extracts. The results reveal that all the extracts of C. rottleri at 250mg/kg body weight (1/10th of LD50) shows a significant reduction in cell aberration whereas in methanol extract which is capable of imparting significant protection against mutagenicity induced by EMS as evidenced by the reduction in the percentage of aberrations compared to chloroform and petroleum ether extracts. Therefore, from these studies, it can be concluded that C. rottleri possesses prominent antimutagenic potential which may be attributed to antioxidant constituents such as phenolics, flavonoids, terpenoids, steroids, glycosides, alkaloids, and carotenoids present in the extracts.